Uso de servicios de salud por habitantes en situación de calle, revisión de literatura (2022)
For this search, literature related to the homeless population that made use of health services and from there to be able to determine the causes that promote continuous access to health services and especially those barriers that impede timely and effective access and care. With the purpose of giving a contribution to the repository of the university in the area of ​​health. HE investigated the repositories of the Antonio Nariño University where they found research projects aimed at publicizing the problems of the inhabitants of street in different national contexts. In this search, several investigations including a so-called perception of the street dweller on the nursing care provided by teachers (Yesenia Castro Cely, Natacha Carolina Kuzniar Pérez and Daniel Yesid Poveda González), professors of the nursing faculty published in the year 2020. (1) This research is a cultural review of the care of nursing where they make known the economic and social conditions of the inhabitants of street and how they influence access to health services that work to improve the attention quality. The purpose of the review was to address the inhabitant's perception of street in front of nursing care in a timely and complete manner (1). As a methodology, they carried out an integrated review of literature with a descriptive scope and retrospective study where 12 search equations were built in databases such as p. 5 Pubmed, in relation to the methodology, integrative literature reviews were used that consists of evaluating the quantity and quality of the service (1). To obtain conclusions from this research, selected characteristics were linked of the article with access to health policies giving an approach to the need of the homeless residents and determine what barriers to accessing the health system cause homeless people to stop attending the system responsibly (1)